Synthesis and in situ observation of 3D super lattices of gold nanoparticles using oil-in-water emulsion - Dutta, Ankur; Chakraborty, Jayanta; Bhagavatula L. V. Prasad; Sahu, Puspanjali (Journal of Colloid and Interface Science, 2014)
In this work oil-in-water emulsion has been successfully used as a confined environment to grow 3D superlattices of gold nanoparticles. The superlattices were grown from 5 nm uniform gold nanoparticles using slow destabilization method. The confined environment was created by forming a stable emulsion where the gold colloid suspended in toluene was used as oil phase. Superlattices were also formed in bulk solution using the same slow destabilization method. A comparative study reveals that compact superlattices form more readily inside the emulsion drops as compared to bulk precipitation. The unstable colloid (in bulk or as emulsion) was aged for various periods at 5 degrees C to form more compact superlattices. The best superlattices with sharp corners are observed when the superlattices are formed inside the emulsion and aged for a month. Two key parameters, the incubation temperature and anti-solvent concentration, are optimized to obtain larger superlattices with sharp features. A new method is also demonstrated for in situ observation of superlattice formation using an optical microscope. 2014 Elsevier Inc. All rights reserved.
Keywords: 3D nanocrystal superlattices; In situ observation of superlattice formation; Monodisperse gold nanoparticles; Nanocrystal superlattices